Pengaruh Model Problem Based Learning (PBL) Berbantuan Media Let’s Read terhadap Kemampuan Membaca Pemahaman Pada Siswa Kelas V Sekolah Dasar - Dhya Ariz Azizah; Neneng Sri Wulan; Teten Ginanjar Rahayu (Lembaga Teewan Journal Solutions, 2026)
Reading comprehension is crucial for elementary students to access broader academic knowledge, yet Indonesian students' reading literacy remains low based on national and international assessments. This study investigates the effect of the Problem Based Learning (PBL) model assisted by Let's Read digital media on fifth-grade students' reading comprehension skills. Using a quantitative approach with a quasi-experimental non-equivalent control group design, this study involved 46 students divided into an experimental group (Class V C, n=23) using PBL with Let's Read media and a control group (Class V A, n=23) using the STAD model. Data were collected through essay tests (pretest and posttest) and analyzed using descriptive statistics and independent sample t-tests via SPSS. The results showed a significant increase in the experimental group's mean score from 63.85 to 85.59. The independent sample t-test on posttest scores yielded p < 0.001, indicating a statistically significant difference between the two groups. The N-Gain score test showed that the PBL model with Let's Read media was quite effective (60.8%), while the STAD model was ineffective (22.9%). The coefficient of determination (R²) confirmed that the treatment contributed 26.1% to reading comprehension improvement. In conclusion, the integration of the PBL model and Let's Read digital media significantly enhances reading comprehension skills in primary education.